Neoadjuvant intra-arterial chemoembolization improves tumor pathological regression and survival in Borrmann type IV gastric cancer - Xiao-Xing Wu; Hou-Dun Yang; Jiang Min; Chao Yuan; Lian-Shuo Li; Wei Zhang; Yue Tong (World Journal of Clinical Oncology, 2026)
BACKGROUND Gastric cancer (GC) is a significant global health challenge with high mortality rates. Borrmann type IV GC presents unique challenges owing to its aggressive biological characteristics and lack of specific clinical symptoms in the early stage, thus leading to advanced-stage diagnosis and poor prognosis. AIM To explore intra-arterial chemoembolization (IAC) as a novel treatment strategy for Borrmann type IV GC. METHODS We retrospectively analyzed 70 patients who underwent IAC followed by gastrectomy. The primary endpoints were overall survival (OS) and disease-free survival (DFS). The secondary outcomes included chemotherapeutic response, toxicities, pathological regression, postoperative morbidity, and mortality. Cox regression analysis was performed to identify independent prognostic factors for Borrmann type IV GC. RESULTS Seventy patients received neoadjuvant IAC followed by gastrectomy with a favorable safety profile (grade ≥ 3 adverse events: 8.6%). The objective response rate was 40.0%, with 20.0% of patients achieving pathological complete response (ypT0) and 52.9% achieving lymph node clearance (ypN0). The median OS and DFS were 21.0 months and 19.0 months, respectively, with 3-year OS and DFS rates of 40.3% and 40.0%, respectively. Regional lymph node regression (N-stage regression) was a significant independent protective factor for both OS and DFS regardless of the primary tumor response. Furthermore, objective pathological regression (complete/partial response) showed a potential association with improved survival. CONCLUSION Neoadjuvant IAC followed by D2 gastrectomy is a safe and highly effective strategy for the treatment of Borrmann type IV GC.